Navigating Investors Activism: The Impact of Boycotts on Indonesian Top FMCG Companies’ Financial Performance - Mivaldo Razaq Wardana Saleh; Raden Aswin Rahadi (Journal Integration of Management Studies, 2025)
This research analyzes the financial and market performance of Top-tier Indonesian Fast-Moving Consumer Goods (FMCG) companies, such as PT Unilever Indonesia Tbk. (UNVR), PT Indofood CBP Sukses Makmur Tbk. (ICBP), and PT Mayora Indah Tbk. (MYOR), over the financial years 2022 to 2024, particularly concerning a consumer boycott movement in response to the Israel- Palestine conflict. The research utilizes a quantitative-comparative methodology, incorporating financial ratio analysis, ESG risk scoring, and sentiment assessment to assess the influence of activist-driven market dynamics on corporate valuation and investor perception. The findings indicate a significant deterioration in UNVR's financial condition, marked by decreased earnings, weakened liquidity, and increased leverage, attributed to reputational harm and adverse consumer sentiment. In contrast, ICBP and MYOR remained financially resilient and grew, driven by ethical consumerism, a localized brand identity, and operational efficiency. The study highlights the inadequacies of traditional financial metrics in identifying risks associated with activism and stresses the importance of adopting a more comprehensive framework that incorporates sociopolitical factors, digital mobilization, and sensitivity to environmental, social, and governance (ESG) issues. The insights presented enhance the comprehension of investor activism and reputational risk within emerging markets while also providing strategic implications for corporate crisis management, investor evaluation frameworks, and regulatory considerations. These findings offer valuable insights into corporate governance practices and investor strategies, especially in politically sensitive markets.